KENJŌGO USAGE FACTOR ON JAPANESE POLITICIAN’S INSTAGRAM RELATED TO COVID 19 - Firda Amelia Noor; Arianty Visiaty (Chi'e: Journal of Japanese Learning and Teaching, 2022)
This study aims to analyze the factors of the use of the kenjōgo 謙譲語 honorification used by the Prime Minister of Japan with the theory of tachiba 立場 by Yasuko Obana. The object of the study used was the Instagram status of two Japanese Prime Ministers. They had served, especially during the start of the COVID-19 pandemic, Shinzo Abe and Suga Yoshihide. The method used in this study is descriptive qualitative, aimed at describing the circumstances that occur in the object of study. The covid 19 pandemic gives the Prime Minister in Japan a great responsibility to make policies that can ensure the safety of the people. Social media such as Instagram is one of the media in conveying policies by prioritizing appropriate language to show a role that matches his identity, namely as prime minister. The results showed that the delivery of policies towards covid-19 countermeasures through Instagram by the Prime Minister of Japan using keigo 敬語, especially kenjōgo 謙譲語 based on the identity of the role (yakuwari, 役割) by giving distance (kyori, 距離) as a sign of respect to the Instagram followers of the Prime Minister of Japan, namely the Japanese people and strengthening the arguments presented through Instagram status. Keywords : Jurnal Pendidikan Bahasa Jepang Japanese Education Journalkenjogoyakuwarijapanese linguisticJapanese studies